“Membangun Budaya Positif Berinternet Berbasis Etika dan Kewarganegaraan serta Meningkatkan Kesadaran Masyarakat di Era Digital” (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In an increasingly advanced digital era, it is important to build a positive internet culture based on ethics and citizenship in order to increase public awareness in the digital era. Values education and digital citizenship play an important role in shaping responsible and positive online behavior. Through values education, the younger generation can be prepared to become global citizens who are aware of the impact of their online actions. Ethical and responsible behavior in using digital technology is key in creating a safe and positive online environment. By building a responsible digital culture, we can reduce the spread of misinformation, hate speech and harmful content, creating a harmonious digital space for all users. Responsible digital citizenship is increasingly important in today’s digital era as technology has become an integral part of everyday life. With awareness of the importance of digital citizenship, the younger generation can use technology positively and contribute to the progress of the digital era. By building a positive internet culture based on ethics and citizenship, we can create an online environment that is inclusive, safe and responsible for all users.